Stimulasi Fission Reproduksi Aseksual Teripang Holothuria atra dan Teripang Holothuria impatiens - Nugroho, David; Hartati, Retno; Suprijanto, Jusup (977-2407769)
Natural production of sea cucumbers in decline, it is because of overfishing and use without any attempt for cultivation. There are several ways for the provision of seeds, one with a reproduction. Sea cucumbers can reproduce sexually and asexually. Sexual reproduction involves the sea cucumber sperm and egg cells, and that asexual reproduction through fission technique. Fission is the process of cleavage of the specimen the anterior, middle and posterior to the sea cucumber. The third part will grow into new individuals after each specimen was able to grow the missing part. The research was conducted on April-June 2012 at Bandengan, Jepara with the aim of analyzing the ability of the sea cucumber Holothuria fission reproduction impatiens and Holothuria atra and observe individual performance and survival of fission results from the fission through the stimulation of 1, 2, and 3 fission plane in sea cucumber Holothuria atra and Holothuria impatiens for the supply of seed. The method used was field experimental research. The results of this research showed stimulation of fission with 1 fission plane is faster than 2 fission plane and 3 fission plane. H. atra to fission faster than H. impatiens. On the stimulation of 2 fission plane, the anterior fission faster than the middle or posterior. The results of regeneration of the species H. impatiens are not able to regenerate. The posterior regenerate faster than the anterior and middle. The posterior regenerate faster than the anterior and middle. In general, sea cucumbers which were going through the stimulation of fission stage, wound closure phase, the stage of regeneration, which in turn will form the mouth and anus on the part of the divide.